FAMILY RESILIENCE AND ROLE NEGOTIATION AMONG KAILI WOMEN IN CENTRAL SULAWESI, INDONESIA - Jusmiati Jusmiati; Suraya Attamimi; Muhammad Zakir Husain; Darlis Darlis (Al-Qalam, 2026)
This study examines the dynamics of family resilience and role negotiation among Kaili women in CentralSulawesi, Indonesia, within socio-cultural, economic, and ecological contexts. Using a qualitativeinterpretive approach grounded in family resilience theory and gender analysis, data were collectedthrough in-depth interviews and observations involving six Kaili women from Palu City and DonggalaRegency. The findings reveal that Kaili women play a central role in sustaining family resilience throughthree primary mechanisms: emotional regulation, their role as guardians of family cohesion, and theinternalization of cultural values that underpin family resilience. Emotional regulation enables women tomanage conflict constructively and maintain family stability, while flexible role negotiation facilitates theequitable distribution of responsibilities between husbands and wives. Furthermore, family resilience isstrengthened by local cultural concepts such as bulonggo and taiganja, which position women as centralfigures in the maintenance, continuity, and well-being of family life. The study finds that resilience amongKaili families is not merely an individual psychological capacity but a relational and culturally embeddedprocess shaped by collective values, kinship relations, and indigenous belief systems. By integratinginsights from family psychology, gender studies, and local wisdom, this study contributes to acontextualized understanding of resilience that challenges individualistic paradigms and highlights itscollective, gendered, and culturally grounded dimensions.